Peningkatan Pemecahan Masalah Siswa Kelas 3 SD Negeri 02 Rowosari Kecamatan Ulujami menggunakan Model Problem Based Learning - Riska Melanti (Jurnal Kualita Pendidikan, 2023)
The ability to solve problems is one of the important abilities to be learned and important to be mastered by students. Aini and Siswono (2014) state that solving math problems is an important part of learning mathematics. improving problem solving for grade 3 students at SD Negeri 02 Rowosari Subdistrict Ulujami using the PBL model. This research is a Classroom Action Research (CAR) using the research design model of Kemmis and Mc Taggart (1988). The subjects of this study were all 3rd grade students of SD Negeri 02 Rowosari, Ulujami District, Pemalang Regency, semester 1 of the 2022/2023 academic year, totaling 24 students. The results of this study are that there is an increase in the problem solving of solving student material based on the stages of Polya through 2 cycles with each cycle consisting of 2 meetings.